Innovative solutions for prehistoric paintings - atmospheric pressure plasma and phosphate consolidant for the preservation of the Magura Cave (Bulgaria). Issue 1 (November 2020) - Stefanova, M; Kamenarov, Z; Sassoni, E; Franzoni, E; Ripà, M; Patelli, A; Sakaj, M; Scopece, P; Verga Falzacappa, E
Abstract: The present study tackles the problem of a sustainable and efficient conservation of cave art, by using innovative materials and techniques for the different steps of the restoration process - Biodeactivation, Biocolonization prevention and Consolidation. The Magura cave in northwest Bulgaria is the case study. It contains an impressive display of prehistoric paintings made of guano as far back as 5'500 years ago. In the last forty years the cave suffered progressive microbial colonization. The detrimental effects are biofilm formation, physical penetration into the stone and chemical reaction with the stone/paintings by pigments. Therefore, as a first step, we investigated biodeactivation by non-thermal plasma sterilization. The oxidative atmosphere obtained introducing Ar/O2 (0.2 and 0.1) in the plasma device, was carried out on lab samples inoculated with the targeted for Magura Cave microorganisms. The main advantage of the non-contact treatment with atmospheric pressure plasma (APP) is the lack of any mechanical and chemical modification of the underlying stone/guano layers. As for sterilization of wounds on human skin the plasma treatment on wet surfaces produces mainly hydrogen peroxide and nitrates which lead to a localized reduction of the pH. The obtained biodeactivation is assured without heat (< 40 °C), toxic and environmentally harmful liquid. In a second step, we tested two possible alternatives for consolidation of the cave. A commercial ethyl silicate (ES) product was compared with an innovative phosphate treatment, based on application of a hydro-alcoholic solution of a phosphate salt (diammonium hydrogen phosphate, DAP). The consolidation efficiency and compatibility of the ES and DAP consolidants were investigated on samples representative for the Magura Cave substrate, i.e. stone alone and stone covered with guano to resemble the prehistoric drawings. In addition, a combination of plasma activation of the stone surface and consolidation was tested, to investigate whether the two treatments may have a synergistic effect, thus making the combined treatment more efficient than consolidation alone.